Effect of pre-treatment and sowing depth towards germination of Coriandrum sativum and Lathyrus odoratus seeds / Muhammad Izzul Muhaimi Awang Hin and Nor'aishah Abu Shah - Awang Hin, Muhammad Izzul Muhaimi; Abu Shah, Nor'aishah (UiTM Cawangan Negeri Sembilan, 2022)
Seed germination has recently reinvigorated interest, owing to its importance in the natural development of plants and the cultivation of crops. However, germination of seeds, especially Coriandrum sativum and Lathyrus odoratus, can sometimes be difficult or impossible due to multiple factors, such as the condition of the seeds themself. The purpose of this study is to examine the effect of pre-treatment on the germination of Coriandrum sativum and Lathyrus odoratus seeds. The experiment was set up in a completely randomized design involving three replicates. The treatments were soaked in tap water for 48 hours (Type A), in tap water for 24 hours (Type B), 6% H2O2 (Type C), abrasion with sandpaper (Type D), scarification with mortar and pestle (Type E), and control (no pre-treatment) (Type F). The most suitable depth level for seed germination and seedling growth of Coriandrum sativum and Lathyrus odoratus were also investigated. The results show that germination of Coriandrum sativum was highest (93.3±6.67) when immersed in 6% hydrogen peroxide (H2O2), while the germination percentage of Lathyrus odoratus was highest (46.7±17.64) when immersed in tap water for 48 hours. Furthermore, Coriandrum sativum seedlings germinated efficiently at a depth of 2.0 cm, while seedlings of Lathyrus odoratus have the highest germination percentage at 0.0 cm (control). Hence, this study can provide useful information about the influence of pre-treatment and sowing depth on the germination of these two plant species, which can directly improve the germination process.